Respuesta :

Answer:

[tex]f^{-1}(x)=\frac{x+15}{3}[/tex]

or

[tex]f^{-1}(x)=\frac{x}{3}+5[/tex]

Step-by-step explanation:

That means we want to find the inverse function of f(x)=3x-15.

The inverse function is just the swapping of x and y really.  We tend to remake the y the subject afterwards.  

So we are given:

y=3x-15

First step: Swap x and y

x=3y-15

Now it's time to solve for y.

Second step: Add 15 on both sides:

x+15=3y

Third step: Divide both sides by 3:

(x+15)/3=y

The inverse function is:

[tex]f^{-1}(x)=\frac{x+15}{3}[/tex]

You can also split up the fraction like so:

[tex]f^{-1}(x)=\frac{x}{3}+\frac{15}{3}[/tex]

The last fraction there can be reduced:

[tex]f^{-1}(x)=\frac{x}{3}+5[/tex]